2010
DOI: 10.1002/polb.21953
|View full text |Cite
|
Sign up to set email alerts
|

Rheological properties of crystallizing polylactide: Detection of induction time and modeling the evolving structure and properties

Abstract: Linear viscoelastic properties of polymer melts are highly sensitive to any structural changes, including molecular weight changes and the formation and growth of crystallites. Here, we make use of this sensitivity to study the homogeneous crystallization of polylactide. As this polymer is rather quickly susceptible to thermal degradation even at moderate temperatures, it is essentially impossible to study homogeneous crystallization in the absence of degradation. Thus, the evolution of complex viscosity of a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
27
1

Year Published

2012
2012
2017
2017

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 21 publications
(30 citation statements)
references
References 47 publications
(59 reference statements)
2
27
1
Order By: Relevance
“…PLA, being a slow crystallizing polymer having a relatively long induction time of crystallization and a low spherulitic growth rate, does not experience noticeable crystallization during cooling from the melt at a 10 °C min -1 cooling rate, unless a nucleating agent or interface having sufficient nucleating activity is present. [39] For the binary system under investigation, the PLA/EBA-GMA interface can play the role of nucleator facilitating crystallization during cooling ( Figure 5). The small amount of chain extender does not allow it to form a separate phase.…”
Section: Observation Of Interface Nucleation Phenomenon By Dscmentioning
confidence: 99%
“…PLA, being a slow crystallizing polymer having a relatively long induction time of crystallization and a low spherulitic growth rate, does not experience noticeable crystallization during cooling from the melt at a 10 °C min -1 cooling rate, unless a nucleating agent or interface having sufficient nucleating activity is present. [39] For the binary system under investigation, the PLA/EBA-GMA interface can play the role of nucleator facilitating crystallization during cooling ( Figure 5). The small amount of chain extender does not allow it to form a separate phase.…”
Section: Observation Of Interface Nucleation Phenomenon By Dscmentioning
confidence: 99%
“…PLA has good mechanical properties, thermal plasticity, and biocompatibility, thus being a promising polymer for various end‐use applications 4–6. However, some drawbacks, such as brittle nature and a lack in toughness, poor thermal stability, and melt strength, are disadvantageous in practical processing especially in the film extrusion industry.…”
Section: Introductionmentioning
confidence: 99%
“…When embryos start to emerge, some polymer chains are engaged in the embryos making the embryos assume a multiarm-like structure [22], while other chains that are not involved in the embryos still maintain their isotropic configurations as in a normal amorphous melt. The polymer chains of the former category occupy a volume fraction of f. Therefore, the rate of the formation of an embryo should be proportional to the volume fraction of the amorphous melt, 12f , with an embryo formation rate constant of k 1 .…”
Section: Rheological Model For Quiescent Crystallization With Low Crymentioning
confidence: 99%
“…Another approach is to define the induction time as the moment when an abrupt upturn in the viscosity curves is perceived [20,21]. Yuryev and Wood-Adams [22] modeled the viscoelasticity of the melts by an exponential decay and defined the induction time by the deviation of the properties from the model when a monotonic increase in the viscoelasticity was brought in by crystallization. Chen et al [23] observed that the normal force was more sensitive to the onset of crystallization than viscosity and defined the induction time as the time when the normal force was twice its initial value.…”
Section: Introductionmentioning
confidence: 99%